The Framework for Comprehensive Forensic Study of Phaleristic Items - G. G. Bocharov (Теория и практика судебной экспертизы, 2021)
The article substantiates the need for a comprehensive forensic examination of phaleristic items – orders, medals, and other badges of distinction involved in the sphere of legal proceedings on criminal, civil, arbitration cases, and cases of administrative offenses. The article notes the features of forensic research of state awards of the RSFSR, the USSR, and the Russian Federation, which result from their specific legal status and normatively fixed manufacturing enterprises.The legitimacy of using the concept of “authenticity” in forensic experts’ conclusions concerning state awards and other subjects of phaleristics has been substantiated. The question of authenticity is crucial and, at the same time, one of the most challenging questions in the research of phaleristic items. Its solution requires assessing all the item’s basic properties and, in many cases, the study of a significant amount of reference and historical material.The features of the use of specialized knowledge of history, forensic traceology, forensic examination of materials, substances, and products, forensic merchandising examination, forensic technical examination of documents in the course of phaleristic objects’ forensic study are analyzed. The author provides methodological recommendations for determining the sequence of conducting various types of research, formulating conclusions based on the results of a comprehensive study, and drawing up expert opinions.